Responses of Subantarctic Marine Phytoplankton to Ozone Decrease and Increased Temperature - Hernando, Marcelo Pablo; Malanga, Gabriela Fabiana; Almandoz, Gaston Osvaldo; Schloss, Irene Ruth; Ferreyra, Gustavo Adolfo (Springer, 2018)
Fil: Hernando, Marcelo Pablo. Comisión Nacional de Energía Atómica; Argentina